2008
DOI: 10.1507/endocrj.k08e-111
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Galectin-9 in the Human Uterodome

Abstract: Abstract. Galectin-9 has been recently considered as a novel marker for the mid-and late-secretory phases of human endometrium and decidua. The aim of this study was to investigate the subcellular distribution of galectin-9 in the endometrial epithelium, especially during the frame of the implantation window. Endometrial biopsies in the proliferative, early, and mid-secretory phases from women with regular menstrual cycle were studied using several approaches, including scanning electron microscopy, immunostai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…This is similar to observations in humans (41), and the distinct expression of LGALS9 during the window of implantation has been suggested to play a potential role during embryo implantation (48). One of the characteristic processes of implantation is immunomodulation, which is characterized by an influx of immune cells at the implantation site (49).…”
Section: Pibf and Galectins In The Bovine Uterussupporting
confidence: 85%
See 3 more Smart Citations
“…This is similar to observations in humans (41), and the distinct expression of LGALS9 during the window of implantation has been suggested to play a potential role during embryo implantation (48). One of the characteristic processes of implantation is immunomodulation, which is characterized by an influx of immune cells at the implantation site (49).…”
Section: Pibf and Galectins In The Bovine Uterussupporting
confidence: 85%
“…In the current study, we showed that LGALS9 was only expressed in the epithelial cells, which is similar to the localization pattern of LGALS15 in the ovine endometrium (31). Although an integrin ligand for LGALS9 has yet to be identified (48), signaling through integrins may be one of the ways in which LGALS9 may function in cattle to mediate the process of implantation.…”
Section: Pibf and Galectins In The Bovine Uterussupporting
confidence: 82%
See 2 more Smart Citations
“…Supporting a reproductive role for Gal-9, M von Wolff et al and Popovici et al found that human endometrium and decidua express Gal-9 and it’s strong expression suggest a potential role during implantation [19][21]. In this regard, it is possible that TIM-3/Gal-9 interaction could play an important role in the regulation of maternal immune tolerance toward the fetus and may be a potent regulator of the adaptive and innate immune responses.…”
Section: Introductionmentioning
confidence: 97%